RICA 2020
DOI: 10.20937/rica.53357
|View full text |Cite
|
Sign up to set email alerts
|

Mining Applications of Immobilized Microbial Cells in an Alginate Matrix: An Overview

Abstract: Immobilized microbial cells have been used extensively in various industrial processes. However, immobilized cells have not been used widely for mining industrial applications. Cell immobilization consists of a technique by which microorganisms are confined through physical or chemical interactions in a matrix, or fixed to the surface of the immobilizing agent. In recent years, entrapment of cells within spheres of Ca 2+ alginate has become the most widely used technique for immobilizing living cells. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…The natural origin of alginate, its biocompatibility, low toxicity, easy gelling operation and inexpensiveness encourage its applications in biotechnological, medical and environmental usages. Furthermore, the research presented in [ 87 ] reinforces this point of view. In this study, it was shown that the entrapment of cells in a suitable matrix would increase the retention time of the cells in wastewater; consequently, the treatment process would be simplified.…”
Section: Discussionsupporting
confidence: 55%
“…The natural origin of alginate, its biocompatibility, low toxicity, easy gelling operation and inexpensiveness encourage its applications in biotechnological, medical and environmental usages. Furthermore, the research presented in [ 87 ] reinforces this point of view. In this study, it was shown that the entrapment of cells in a suitable matrix would increase the retention time of the cells in wastewater; consequently, the treatment process would be simplified.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, natural/ non-synthetic origin of alginate hydrogel contributed in successful degradation process by its low toxicity and biocompatibility traits. Therefore, entrapment in alginate matrix was frequently employed in biotechnological, medical and environmental applications [ 92 ]. Several researches addressed a successful bioremediation of azo dyes by microbial immobilization technique [ 93 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…The considerable economic value and numerous industrial uses make biorecovery of rare-earth elements through biosorption appealing. Thus, the biosorption serves as an outstanding cost-effective method for the recovery of rare earth metals from aqueous solutions and a biotechnological innovation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%